THE VIEWS OF NURSES ON THE VULNERABILITY OF THE ADOLESCENTS IN A HEALTH DISTRICT - Melissa dos Reis Pinto Mafra; Maria Marta Nolasco Chaves; Liliana Muller Larocca; Laura Christina Macedo Piosiadlo (Universidade Federal do Paraná, 2015)
This exploratory research with a qualitative character, grounded in the Theory of Nursing Praxis Intervention in Collective Health, aims to identify the adolescents' vulnerabilities according to the view of nurses of a Health District. The data were collected using semistructured interviews held with 16 nurses in February - March 2014, these being analyzed through content analysis, using the webQDA software. Evidence was found for four categories and sixteen subcategories, with emphasis placed on the recognition of vulnerabilities among the adolescents. In the social construction, it is naturalized that boys and girls have different vulnerabilities in the territory. Therefore, for interventions, the training of the professionals and support from the management is necessary such that their needs may be met in interdepartmental actions. It is concluded that studies are necessary which discuss, in the light of gender, the process of determination of the adolescents' vulnerability, so as to instrumentalize intervention projects which lead to overcoming these vulnerabilities.